Thymineless death, at the origin - Guzmán, Elena C.; Martín, Carmen M. (Frontiers in Microbiology, 2015)
Thymineless death (TLD) in bacteria has been a focus of research for decades. Nevertheless, the advances in the last five years, with Escherichia coli as the model organism, have been outstanding. Independent research groups have presented compelling results that establish that the initiation of chromosome replication under thymine starvation is a key element in the scenario of TLD. Here we review the experimental results linking the initiation of replication to the lethality under thymine starvation and the proposed mechanisms by which TLD occurs. The concept of this relationship was ‘in the air’, but approaches were not sufficiently developed to demonstrate the crucial role of DNA initiation in TLD. Genome-wide marker frequency analysis and Two Dimensional (2D) agarose gel electrophoresis have been critical methods employed to reveal that initiation events and the degradation of the oriC region occur during thymine starvation. The relationships between these events and TLD have established them to be the main underlying causes of the lethality under thymine starvation. Furthermore, we summarize additional important findings from the study of different mutant strains, which support the idea that the initiation of chromosomal replication and TLD are connected.